2017
DOI: 10.1186/s13041-016-0282-7
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of intermittent hypoxia increases phosphorylated tau in the hippocampus via biological processes common to aging

Abstract: Sleep-disordered breathing produces cognitive impairments, and is possibly associated with Alzheimer disease (AD). Intermittent hypoxia treatment (IHT), an experimental model for sleep-disordered breathing, results in cognitive impairments in animals via unknown mechanisms. Here, we exposed mice to IHT protocols, and performed biochemical analyses and microarray analyses regarding their hippocampal samples. In particular, we performed gene ontology (GO)-based microarray analysis to elucidate effects of IHT on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 84 publications
0
30
1
Order By: Relevance
“…We have previously reported that chronic hypoxia aggravated Aβ production though epigenetic modifications of γ-secretase (Liu et al, 2016 ) and induced autophagy in AD mouse model (Liu et al, 2015 ). Other studies have confirmed that hypoxia could increase tau phosphorylation (Zhang et al, 2014 ; Yagishita et al, 2017 ). Furthermore, our group and others have demonstrated that hypoxia can significantly activate microglia which is believed to play an important role in the pathogenesis of AD (Zhang et al, 2013 ; Sapin et al, 2015 ).…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…We have previously reported that chronic hypoxia aggravated Aβ production though epigenetic modifications of γ-secretase (Liu et al, 2016 ) and induced autophagy in AD mouse model (Liu et al, 2015 ). Other studies have confirmed that hypoxia could increase tau phosphorylation (Zhang et al, 2014 ; Yagishita et al, 2017 ). Furthermore, our group and others have demonstrated that hypoxia can significantly activate microglia which is believed to play an important role in the pathogenesis of AD (Zhang et al, 2013 ; Sapin et al, 2015 ).…”
Section: Discussionmentioning
confidence: 77%
“…Hypoxia, as one of the environmental risk factors, was reported to contribute to the pathogenesis of AD (Zhang and Le, 2010 ). Previous studies have indicated that hypoxia may increase Aβ production (Li et al, 2009 ), decrease Aβ degradation (Wang et al, 2011 ) and enhance tau phosphorylation (Gao et al, 2013 ; Yagishita et al, 2017 ), thereafter may further aggravate the pathological changes of AD. Hypoxia is also reported to be associated with neuroinflammation.…”
Section: Introductionmentioning
confidence: 99%
“…Hypoxia has been reported as one of the important environmental risk factors of AD. Many studies have confirmed that hypoxia facilitates AD pathological changes (Shiota et al, 2013 ; Liu et al, 2015 ; Yagishita et al, 2017 ; Zhang et al, 2017 ). In the present study, we demonstrated the impacts of acute hypoxia on AD-like pathologies including Aβ and tau pathologies, dysregulated autophagy, mitochondrial dysfunction and neuroinflammation.…”
Section: Discussionmentioning
confidence: 91%
“…Although several reports have described biochemical and neurophysiological changes occurring in the hippocampus (Row et al, 2003;Kumar et al, 2009;Xie et al, 2010;Wall et al, 2014;Yagishita et al, 2017), the impact of IH on the dentate gyrus of the hippocampus has been largely been unaddressed. Here we address this issue by examining how IH affects synaptic plasticity and adult neurogenesis in the dentate gyrus.…”
Section: Discussionmentioning
confidence: 99%